1990
DOI: 10.1172/jci114554
|View full text |Cite
|
Sign up to set email alerts
|

The cardiac beta-myosin heavy chain isogene is induced selectively in alpha 1-adrenergic receptor-stimulated hypertrophy of cultured rat heart myocytes.

Abstract: protein and iso-mRNA levels in cultured cardiac myocytes were quantified during hypertrophy stimulated by the a,-adrenergic agonist, norepinephrine (NE). fl-MHC iso-protein content was increased 3.2-fold vs. control (P < 0.001), whereas a-MHC isoprotein content was not changed significantly (1.4-fold vs. control, P = NS). MHC iso-mRNA levels were quantified by nuclease Si analysis, using a single oligonucleotide probe. NE increased fl-MHC iso-mRNA content by 3.9-fold

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
82
1
5

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(102 citation statements)
references
References 58 publications
14
82
1
5
Order By: Relevance
“…Cell Culture and Transfection-Neonatal rat ventricular myocytes (NRVMs) were prepared according to the method described in Waspe et al (28). Briefly, 150,000 cells/well were plated in 12-well tissue culture plates coated with gelatin.…”
Section: Methodsmentioning
confidence: 99%
“…Cell Culture and Transfection-Neonatal rat ventricular myocytes (NRVMs) were prepared according to the method described in Waspe et al (28). Briefly, 150,000 cells/well were plated in 12-well tissue culture plates coated with gelatin.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, by use of primary cultures of cardiac myocytes, it was demonstrated that adenylate cyclase activators and cAMP analogues activate the expression of the αMHC isoform (V1) and the αMHC mRNA transcript [66,67]. The α1-adrenergic agonists or activators of the PK-c pathway, on the other hand, led to increased expression of the V3 myosin isoform and a relative abundance of βMHC mRNA [66,67,76]. However, in an earlier study using cultures of cardiac myocytes grown in a serum-free defined medium, no effect of either β-or α-adrenergic agonists on the expression MHC mRNA was found [77].…”
Section: Role Of Adrenergic Stimulationmentioning
confidence: 99%
“…This finding may be because these genes are exquisitely regulated in vivo by extrinsic factors such as circulatory levels of thyroid hormone and catecholamines, in addition to neuronal input, all of which are difficult to accurately reproduce in cell culture (Waspe et al, 1990;Flink et al, 1992;Kariya et al, 1994). In addition, the ␣ MyHC gene promoter exhibited distinct behavior in vivo when analyzed by direct DNA injection compared with the regulation observed in transgenic mice (Subramaniam et al, 1991;Buttrick et al, 1993).…”
Section: Interplay Between An Upstream Cardiac-enhancer and Proximal mentioning
confidence: 99%